Comparative Study Between Dynamic Navigation System And Guided Endodontics In Access Cavity Preparation - Hassanein, Ihab El Sayed; Hussien, Shady Ali; Lotfy El Gharib, Mahmoud (Journal of Neonatal Surgery, 2025)
Aim :. The aim of the present study was to compare between two computer guided access cavity designs: Dynamic Navigation Access and Guided Access with Traditional Access Cavity in respect to the Procedure time, Percentage of hard tissue removal. Methods: forty-five 3D printed maxillary first permanent molar were divided into three groups: Group I (Dynamic navigation guided access), Group II (static guided access) Group III (conventional access). CBCT scans taken for all mounted treatment teeth. Pulp chamber volume is calculated using 3D Slicer. Access cavity was done in each group according to the system used. The time taken during access was recorded in seconds. Afterwards, CBCT scans taken and Pulp chamber volume is calculated using 3D Slicer to assess the amount of dentin lost. Results: There was a significant difference between different groups in access time ,the highest mean time was found in group (III) , followed by group (I) while the lowest time was found in group (II). Regarding percentage of dentin lost there was a significant difference between different groups highest mean lost dentine was found in group (III) followed by group (I) while the lowest value was found in group (II). Conclusion: Static guided access is a time saver with conservative approach.